2020
DOI: 10.22225/jr.6.2.1727.178-185
|View full text |Cite
|
Sign up to set email alerts
|

Interlanguage Analysis on Speech Produced by EFL Learners

Abstract: Indonesian EFL Learners experience erroneous speech in the process of learning the target language. Interlanguage, the errors that contain linguistic features which neither belong to the first language (L1) nor the target language becomes the focus of this study. The study aims to analyze the native and target language influence on the interlanguage produced by the students in their speech production. This study was designed in qualitative research approach. The data was collected through interviewed of 20 eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…From this fact, it can be interpreted that students tend to activate their linguistic knowledge previously learned from the target language (English) and the first language (Indonesia). Kusumawardani (2020) confirms that the students' oral speech influenced by the native language, Indonesian resulting the interlanguage production. In this case, the students use this strategy to keep communication in the target language (English) running even with their limited language skills.…”
Section: Simplificationsupporting
confidence: 62%
“…From this fact, it can be interpreted that students tend to activate their linguistic knowledge previously learned from the target language (English) and the first language (Indonesia). Kusumawardani (2020) confirms that the students' oral speech influenced by the native language, Indonesian resulting the interlanguage production. In this case, the students use this strategy to keep communication in the target language (English) running even with their limited language skills.…”
Section: Simplificationsupporting
confidence: 62%
“…The first intralingual forms were over generalizations of past form -ed. Kusumawardani & Adnyani (2020) confirmed that the cause of overgeneralizations was the students knew that they should add -ed at the end of the verbs indicating past events. In examples (37) to (39), the students failed to notice that the infinitive verb in English did not require the ending.…”
Section: Intralingual Interferencementioning
confidence: 64%
“…Subject deletion is another native language influence on the students' interlanguage. A complete English sentence should consist of a subject and a predicate, and it cannot be said as a complete sentence if the speakers' pattern does not consist of a subject (Kusumawardani & Adnyani, 2020). The following were examples of students' utterances in which they omitted subjects in their sentences.…”
Section: Interlingual Interferencementioning
confidence: 99%
“…It happens when the knowledge of the first language (L1) interferes with the use of the second language (L2). Moreover, language interference can be defined as a circumstance in which the knowledge of a speaker's or a writer's native language is applied to a second language (Alkhateeb, 2016;Kusumawardani & Adnyani, 2020).…”
Section: Introductionmentioning
confidence: 99%